Discovery of TBC1D7 as a Potential Driver for Melanoma Cell Invasion. Issue 14 (2nd July 2020) - Qi, Tianyu F.; Guo, Lei; Huang, Ming; Li, Lin; Miao, Weili; Wang, Yinsheng
Abstract: Metastasis is the leading cause for mortality in melanoma patients. Here, an unbiased mass spectrometry‐based quantitative proteomic method is utilized to assess differential protein expression in a matched pair of primary/metastatic melanoma cell lines (i.e., WM‐115/WM‐266‐4) derived from the same patient. It is found that TBC1D7 is overexpressed in metastatic over primary melanoma cells, and elevated expression of TBC1D7 promotes the invasion of these melanoma cells in vitro, partly through modulating the activities of secreted matrix metalloproteinases 2 and 9. Additionally, interrogation of publicly available data show that higher mRNA expression of TBC1D7 predicts poorer survival in melanoma patients. Together, the results suggest TBC1D7 as a driver for melanoma cell invasion, which is an important element in melanoma metastasis. The proteomic data generated from this study may also be useful for exploring the roles of other proteins in melanoma metastasis.